A Hardware Vehicle Security and Accident Notification System using the Haar Cascade Algorithm - Rafiammal, S. Syed; Parnasree, C.; Ambika, A.; Manaas, M. (IRO Journal on Sustainable Wireless Systems, 2023)
Low-cost vehicle security and accident notification system is essential in this modern society as vehicle theft and accidents that occur are increasing daily. In this proposed system, hardware for vehicle security is implemented, with authentication, and accident notification. Authentication is achieved by face detection and recognition using an open CV. The defaulter information is forwarded to the authenticated mobile number of the person by whom the vehicle is owned, using the GSM module and a notification email. The face authentication module was developed using the discrete wavelet transform-based Haar cascade algorithm. In addition to the face authentication, accident notifications will be sent to family members of the vehicle owner. Micro electrical mechanical system sensor was utilized to detect accident incidents using the accelerometer concept.
Keywords: Haar Cascade Algorithm; Vehicle Management System; Accident Notification; Face Detection